Recommendations for restoration of ancient buildings and the survival of a masonry chimney - Lourenço, Paulo B. (2006)
In the last years significant developments occurred with respect to the possibilities of experimental and numerical analysis of ancient cultural heritage buildings. Such advances result from the societal growing concern about the preservation of this heritage, together with the evident cultural and economic importance of this activity. Recommendations for interventions in architectural heritage structures recently issued by ICOMOS are briefly reviewed here, with a discussion about the proposed methodology. Then, a case study is fully detailed, including the aspects of survey, advanced numerical analysis, diagnosis, justification of remedial measures and detailing of the adopted strengthening. The paper also advocates that significant information can be obtained from numerical analysis, namely with respect to the understanding of existing damage and to the minimum and adequate design of strengthening. A clear understanding of the structural behaviour, based on sophisticated tools of analysis, can therefore reduce the extent of the remedial measures in the restoration of ancient structures. In this case, a masonry chimney with severe damage is strengthened keeping the old fabric, as a significant example that ancient timber and masonry structural elements can often survive if appropriate methodologies for diagnosis and repair measures are adopted.